Hepcidin induces HIV-1 transcription inhibited by ferroportin - Turner Willie; Rotimi Jamie; Foster Altreisha; Kashanchi Fatah; Xu Min; Gordeuk Victor R; Nekhai Sergei (Retrovirology, 2010)
Abstract Background Physiological regulation of cellular iron involves iron export by the membrane protein, ferroportin, the expression of which is induced by iron and negatively modulated by hepcidin. We previously showed that iron chelation is associated with decreased HIV-1 transcription. We hypothesized that increased iron export by ferroportin might be associated with decreased HIV-1 transcription, and degradation of ferroportin by hepcidin might in turn induce HIV-1 transcription and replication. Here, we analyzed the effect of ferroportin and hepcidin on HIV-1 transcription. Results Expression of ferroportin was associated with reduced HIV-1 transcription in 293T cells and addition of hepcidin to ferroportin-expressing cells counteracted this effect. Furthermore, exposure of promonocytic THP-1 cells to hepcidin was associated with decreased ferroportin expression, increased intracellular iron and induction of reporter luciferase gene expression. Finally, exposure of human primary macrophages and CD4+ T cells to hepcidin and iron was also associated with induction of viral production. Conclusion Our results suggest that the interplay between ferroportin-mediated iron export and hepcidin-mediated degradation of ferroportin might play a role in the regulation of HIV-1 transcription and may be important for understanding of HIV-1 pathogenesis.